2023
DOI: 10.1109/tnnls.2021.3123968
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Guided Generative Adversarial Networks for Sea Subsurface Temperature Prediction

Abstract: Sea subsurface temperature, an essential component of aquatic wildlife, underwater dynamics and heat transfer with the sea surface, is affected by global warming in climate change. Existing research is commonly based on either physics-based numerical models or data based models. Physical modeling and machine learning are traditionally considered as two unrelated fields for the sea subsurface temperature prediction task, with very different scientific paradigms (physics-driven and datadriven). However, we belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The inputs and outputs of the PBML model are first determined by the main variables in the physicsbased wave model, and then machine learning algorithms are used to train and perform multi-step ahead forecasts. A framework based on a combination of GAN and physical numerical models for predicting SST is also used to train the neural network model using the physical-based numerical model and then calibrate the model parameters using observed data (Meng et al, 2021b).…”
Section: Hybrid Physics-ml Modelsmentioning
confidence: 99%
“…The inputs and outputs of the PBML model are first determined by the main variables in the physicsbased wave model, and then machine learning algorithms are used to train and perform multi-step ahead forecasts. A framework based on a combination of GAN and physical numerical models for predicting SST is also used to train the neural network model using the physical-based numerical model and then calibrate the model parameters using observed data (Meng et al, 2021b).…”
Section: Hybrid Physics-ml Modelsmentioning
confidence: 99%
“…Therefore, joining the complementary merits of multisource data further improves the accuracy of land-cover classification [19]. In the past decade, extensive classification techniques have been successfully applied to multisource data [20][21][22]. Some of the machine learning methods rely on support vector machine (SVM), extreme learning machine (ELM) and random forest (RF) [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al (Lu et al, 2019) reported a combined pre-clustering process and a neural network approach to determine STAs by using ocean surface temperature, surface height, surface wind observations and gridded monthly Argo data. Meng et al (Meng et al, 2021) proposed a generative adversarial network (GAN)based framework combined with a numerical model to predict sea subsurface temperature. In addition, popular deep learning algorithms, such as convolutional neural networks (CNNs), long short-term memory (LSTM) neural networks, extreme gradient boosting (XGBoost) and light gradient boosting machine (LightGBM), have also been adopted to invert ocean interior thermal structures from multisource satellite observations (Han et al, 2019;Su et al, 2019;Su, Wang, et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum number of training epochs is set to 200, and the model with the best performance on the validation dataset is saved as the final model.Second, the trained model at each depth level was fine-tuned with satellite remote sensing data and CORA 2.0 data. Meng et al(Meng et al, 2021) used daily Argo data to fine-tune a trained model which can improve the model performance. However, our study areas are the marginal sea of China with only a few Argo buoys at the edge of the ECS.…”
mentioning
confidence: 99%